PENCEGAHAN STUNTING DARI MASA KEHAMILAN: EDUKASI PADA IBU HAMIL DI DESA PURBAYAN KECAMATAN BAKI - Aulia Fahriza Rahmawati; Dian Maharrani; Abrizal Naufal Aqila; Satiy Annisa Fakita; Elsa Fara Islamiyah; Aldhi Rangga Saputra; Putri Wulandari; Siska Fitowi Rantini; Aliya Rahma Latifa; Sandiva Budi Normalia; Yuli Kusumawati; Wahyu Tri Sudaryanto (Universitas Muhammadiyah Surakarta, 2024)
The results of the situation analysis, there are still pregnant women who do not know about stunting, the causes of stunting and the consequences of stunting. This community service activity aims to provide education about stunting prevention from an early age during pregnancy. The method of this community service activity with pregnant women and posyandu cadres in Purbayan Village, Baki District was carried out using the lecture and question and answer method, the activity was carried out through several stages, including: (1) field survey; (2) preparation for the implementation of activities; (3) pregnancy health checks; (4) pregnancy exercise; (5) pre-test; (6) stunting education; (7) discussion; (8) post-test. To evaluate this activity using pretest and posttest with Power Point Presentation media. The results of the activity showed that in the pretest, 1 person scored in the category of not understanding, 16 people in the category of not understanding, and 1 person in the category of understanding. After being given education there is an increase in value from the results of the pre test to the post test. There are 2 people getting scores in the less understanding category and 16 people in the understanding category. Conclusion: providing education about preventing stunting during pregnancy can increase knowledge about stunting in pregnant women in Purbayan Village.